Systematic Use Of Mathematical Concepts In Professional Training Of Students (Journal of Pharmaceutical Negative Results, 2023)
The article provides the mathematical concepts in the process of vocational guidance of students in higher education, the specifics of teaching higher mathematics based on the characteristics of the educational direction. Today, the higher education system is characterized by the development of intellectual potential, independent thinking and decision-making, and the creation of new generations of science programs is important to achieve this goal.